Nigrosine particle powder, resin composition using the same, and aqueous dispersion
By coating the aniline black particle powder of alkali-soluble resin, the problem of excellent blackness and time stability in synthetic leather coatings is solved, and the effect of preventing viscosity and gelation in the aqueous dispersion is achieved.
Patent Information
- Application Number
- CN202180024333.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-24
- Filing Date
- 2021-01-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-01-21
AI Technical Summary
In the use of synthetic leather coatings and the like, the prior art is difficult to provide aniline black particle powder with excellent blackness and the ability to prevent the coating from sticking and gelling over time, especially when high molecular weight water-based polyurethane resin is used.
By coating aniline black particle powder with an alkali-soluble resin, the acid value is 150-350 mgKOH/g, and the coating amount is 3-15% by weight, so as to prevent direct contact with the aqueous polyurethane resin, thereby inhibiting the viscosity and coagulation of the coating. Glued.
When used in an aqueous dispersion, the aniline black particle powder has excellent performance in the time stability and blackness, the viscosity increase rate is 10% or less, the yield value is 0.1Pa or less, and the brightness L* value is 15.0 or less.
Smart Images

Figure BDA0003863445600000151 
Figure BDA0003863445600000161 
Figure BDA0003863445600000181
Abstract
Description
Technical Field
[0001] The present invention relates to aniline black particle powder having excellent blackness and excellent temporal stability when used in an aqueous dispersion.
[0002] The present invention also relates to a polyurethane resin composition colored with the aniline black particle powder, and also relates to an aqueous dispersion containing a water-soluble polyurethane resin that can contain the aniline black particle powder at a high concentration and has excellent stability over time. Background Art
[0003] Aniline black particles have a characteristic black color and are difficult to dissolve in aqueous or non-aqueous solvents, so they have long been used as black pigments. Aniline black is a type of polyaniline obtained by oxidative polymerization of aromatic amines such as aniline, and can be said to be composed mainly of a basic skeleton based on N-phenyldibenzo-p-pyrazine polymer. On the other hand, linear polyanilines such as emeraldine polymerized at the para position of aniline have green to purple colors and are mainly used as organic conductors.
[0004] As the oxidant used in the manufacture of the above-mentioned aniline black particle powder, dichromate, chlorate, hydrogen peroxide, etc. are currently used, and as the catalyst, copper salt, vanadium oxide, iron salt, etc. are currently used. Among them, the method using dichromate as the oxidant is most suitable for the above-mentioned manufacture. At present, the aniline black particle powder has the advantage of showing a blue-black color that carbon black cannot show. Therefore, taking advantage of the above-mentioned advantages, the aniline black particle powder is used for various purposes such as coatings, printing inks, pigments, poster pigments, plastics, thermal transfer inks, etc.
[0005] Generally, in order to reduce the brightness and gloss of black pigments such as carbon black and further improve the blackness, a technique of coating the surface of the pigment with an insoluble resin is disclosed (Patent Document 1). In addition, a water-based paint is generally known, characterized in that, for a water-based black paint containing a water-soluble polymer substance having a carboxyl group and aniline black, a basic compound is used to adjust the pH to 5.5 to 11.0 in order to suppress the viscosity increase and gelation over time (Patent Document 2).
[0006] However, as a black colorant for purposes such as synthetic leather coatings, almost all carbon black with cheapness and excellent coloring is used. In recent years, in synthetic leather coatings, in order to strengthen the VOC emission restrictions about preventing air pollution or to prevent water pollution, it is obvious to turn to water-based coatings from non-aqueous coatings. The main constituent materials of synthetic leather water-based coatings are water, binder resins, pigments, other additives (crosslinking agents, viscosity regulators, cosolvents, etc.). In the above-mentioned binder resins, in order to give the coating film with flexibility, improve the high functionalization such as the adhesion with the substrate for the purpose, use water-soluble polyurethane resins. The above-mentioned water-soluble polyurethane resins are polyether diols, polyester diols, polycarbonate diols resins, which are appropriately selected and used according to the purpose.
[0007] In order to improve the blackness, when aniline black is used as a colorant in a water-based polyurethane coating, the resulting coating tends to increase in viscosity and gel over time. In particular, when a high molecular weight water-based polyurethane resin is used in the water-based coating, the resulting coating has a significant tendency to do so.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 10-60314
[0011] Patent Document 2: Japanese Patent Application Publication No. 2002-60647 Summary of the invention
[0012] Technical problem to be solved by the invention
[0013] As mentioned above, in the use of synthetic leather coatings, it is required that the nigrosine particles have excellent blackness and can prevent the viscosity increase and gelation over time when the coating is made. In addition to the use of printing inks, the above-mentioned coatings are also gradually developed in the use of non-magnetic developers for electronic photography, black matrices for liquid crystals, cosmetics, etc. In addition, in recent years, it is also required that the nigrosine does not contain transition metals such as chromium ions or copper ions. However, for aqueous dispersions containing water-soluble polyurethane resins containing nigrosine, nigrosine particles that can suppress the viscosity increase and gelation over time have not yet been obtained.
[0014] That is, the technical problem of the black pigment described in the above-mentioned patent document 1 is to reduce the lightness and glossiness and improve the blackness, which is different from the technical problem of the present invention. In addition, the coated resin is different from that of the present invention. Therefore, when the water-based paint contains the aniline black described in the above-mentioned patent document 1, it is difficult to say that the viscosity increase and gelation of the paint over time are suppressed. In addition, in the water-based paint containing aniline black described in the above-mentioned patent document 2, since there is direct contact between water and aniline black, it is difficult to say that the viscosity increase and gelation of the paint over time are fully suppressed.
[0015] Therefore, the technical problem of the present invention is to provide a nigrosine particle powder which, when prepared as an aqueous dispersion, suppresses the viscosity increase and gelation of the dispersion over time and has excellent blackness. In addition, the technical problem of the present invention is to provide a polyurethane resin composition having excellent blackness and containing the nigrosine particle powder. In addition, the technical problem of the present invention is to provide an aqueous dispersion containing the nigrosine particle powder, in which the viscosity increase and gelation over time are suppressed.
[0016] Technical solutions to solve problems
[0017] The above technical problem can be achieved by the present invention as follows.
[0018] That is, the present invention provides a nigrosine particle powder, which is a nigrosine particle powder coated with an alkali-soluble resin, characterized in that the acid value of the alkali-soluble resin is 150 to 350 mgKOH / g, and the coating amount of the alkali-soluble resin is 3 to 15% by weight. (Present invention 1)
[0019] In addition, according to the aniline black particle powder of the present invention 1, the alkali-soluble resin is one or more resins selected from styrene-acrylic acid copolymers, styrene-maleic acid copolymers and rosin-modified resins. (Present invention 2)
[0020] In addition, according to the aniline black particle powder of Invention 1 or 2, the average particle size of the primary particles is 0.05 to 1.0 μm. (Invention 3)
[0021] The present invention also provides a polyurethane resin composition containing the aniline black particle powder according to any one of Inventions 1 to 3. (Invention 4)
[0022] The present invention also provides an aqueous dispersion containing a water-soluble polyurethane resin, which contains the nigrosine particles according to any one of Inventions 1 to 3. (Invention 5)
[0023] Effects of the Invention
[0024] The nigrosine particles of the present invention are nigrosine particles with excellent blackness. When used in an aqueous dispersion, the nigrosine particles do not gel and have excellent stability over time, so they are suitable as black pigments for aqueous dispersions. Specifically, the aqueous dispersion containing the nigrosine particles of the present invention has a viscosity increase rate of 10% or less after storage for 21 days, and a yield value obtained from the viscosity measured after storage for 21 days is 0.1 Pa or less. In addition, the obtained resin composition has excellent blackness, and specifically, the lightness (L* value) is 15.0 or less. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a bright field (BF) image of the nigrosine particle powder obtained in Example 1, taken by a transmission electron microscope (TEM).
[0026] Figure 2 This is a BF image of TEM of aniline black obtained in Comparative Example 1.
[0027] Figure 3 This is a BF image of TEM of aniline black obtained in Comparative Example 8. DETAILED DESCRIPTION
[0028] The construction of the present invention will be described in more detail below.
[0029] First, the nigrosine particle powder of the present invention will be described.
[0030] The nigrosine particles of the present invention are nigrosine particles coated with an alkali-soluble resin. By coating with an alkali-soluble resin, the viscosity increase of the coating can be suppressed. Here, the alkali-soluble resin is any resin that is water-soluble under alkaline conditions (for example, a resin having an acidic group such as a carboxyl group).
[0031] The alkali-soluble resin is, for example, selected from polyacrylic acid, acrylic acid-acrylonitrile copolymer, vinyl acetate-acrylate copolymer, acrylic acid-acrylate copolymer, styrene-acrylic acid copolymer, styrene-methacrylic acid copolymer, styrene-methacrylic acid-acrylate copolymer, styrene-α-methylstyrene-acrylic acid copolymer, styrene-α-methylstyrene-acrylic acid-acrylate copolymer, styrene-maleic acid copolymer, styrene-maleic anhydride copolymer, vinylnaphthalene-acrylic acid copolymer, vinylnaphthalene-maleic acid copolymer, vinyl acetate-maleic acid copolymer, vinyl acetate-crotonic acid copolymer, vinyl acetate-acrylic acid copolymer, rosin-modified maleic acid and rosin-modified fumaric acid. One or more, and their salts can also be used. From the viewpoint of easily adjusting the acid group of the alkali-soluble resin to within the scope of the present invention, it is preferably a copolymer of a unit having an acidic group and a unit not having an acidic group constituting the alkali-soluble resin.
[0032] The alkali-soluble resin in the present invention is more preferably a styrene-acrylic acid copolymer, a styrene-maleic acid copolymer, or a rosin-modified resin having excellent dispersion stability and temporal stability of the pigment.
[0033] The aniline black particle powder of the present invention is aniline black particle powder coated with an alkali-soluble resin, and the acid value of the alkali-soluble resin is 150 to 350 mgKOH / g. By preparing the aniline black particle powder coated with the alkali-soluble resin having an acid value of 150 to 350 mgKOH / g, when preparing an aqueous dispersion, an aqueous dispersion with excellent stability over time can be obtained. In the case where the acid value of the alkali-soluble resin is lower than 150 mgKOH / g, it is difficult to uniformly coat the surface of the aniline black particles in water, which is not preferred. In addition, in the case where the acid value exceeds 350 mgKOH / g, the binder for coating is easily oxidized, and the dispersion stability and color tone stability become poor, which is not preferred. The acid value is preferably 160 to 330 mgKOH / g, and more preferably 170 to 300 mgKOH / g. Examples of methods for adjusting the acid value to fall within this range include appropriately adjusting the copolymerization ratio of units having an acidic group and units having no acidic group constituting the alkali-soluble resin, or increasing or decreasing constituent elements other than carboxyl groups to increase or decrease the molecular weight of the structural unit.
[0034] The nigrosine particle powder of the present invention is a nigrosine particle powder coated with an alkali-soluble resin, and the coating amount of the alkali-soluble resin is 3 to 15% by weight. By preparing the nigrosine particle powder coated with 3 to 15% by weight of the alkali-soluble resin, when preparing an aqueous dispersion, an aqueous dispersion with excellent temporal stability can be obtained. In the case where the above-mentioned coating amount is less than 3% by weight, the nigrosine particles cannot be completely coated, which is not preferred. In addition, in the case where the above-mentioned coating amount exceeds 15% by weight, the coated resin is eluted into the coating, and the viscosity and temporal stability of the coating become poor, which is not preferred. The above-mentioned coating amount is preferably 4 to 14% by weight, and more preferably 5 to 13% by weight.
[0035] The aniline black particle powder of the present invention preferably has a coating layer formed of an alkali-soluble resin with a thickness of 2 to 50 nm.
[0036] The average particle size of the primary particles of the aniline black particle powder of the present invention is preferably 0.05 to 1.0 μm. When the average particle size of the primary particles of aniline black is less than 0.05 μm, the coloring power is low, dispersion is difficult, and there is a tendency for the blackness to deteriorate. In addition, when the average particle size of the primary particles exceeds 1.0 μm, the coloring power is low, and there is a tendency for the blackness to deteriorate. The more preferred average particle size of the primary particles is 0.10 to 0.90 μm.
[0037] The powder pH of the aniline black particle powder of the present invention is preferably in the range of 3.0 to 9.0. When the powder pH is lower than 3.0, it is difficult for the aniline black particles to be uniformly coated with the alkali-soluble resin. The same applies when the powder pH exceeds 9.0. A more preferred powder pH is 3.5 to 8.0.
[0038] The hue of the aniline black particle powder of the present invention can also be evaluated by the hue of the polyurethane resin composition containing the aniline black particle powder of the present invention. That is, the hue of the aniline black particle powder of the present invention can be expressed by the L* value, a* value, and b* value in the chromaticity index of the resin composition measured by the method described below, and the blackness is indicated by the lightness L* value. The L* value is preferably 15.0 or less, and in this case, it can be said that the blackness is excellent. In the case where the L* value exceeds 15.0, it is difficult to say that the blackness is excellent. A more preferred L* value is 14.0 or less. A further preferred L* value is 12.0 or less. In addition, the a* value and the b* value are various depending on the target color, and can be controlled by the reaction mode of the aniline black, specifically, by the particle size, shape, and the type and amount of the acid group contained. In the case of expressing a normal black color, the a* and b* values are preferably -20 to 20, respectively, but should be controlled according to the target color and are not limited to these values.
[0039] In order to improve the dispersibility and color development, the nigrosine particles of the present invention may contain aromatic compounds other than aromatic amines, heterocyclic compounds, their segments, or substances composed of two or more of them in the composition, or may be copolymerized. Examples of the aromatic compounds include aromatics such as benzene, toluene, xylene, and naphthalene, aromatic acids such as phenol, benzenesulfonic acid, p-toluenesulfonic acid, and benzoic acid, and heterocyclic compounds such as furan, thiophene, and quinone.
[0040] The nigrosine particles of the present invention may be further surface treated to improve dispersibility and color development. The surface treatment agent is not particularly limited, and examples thereof include surfactants such as alkanols, fatty acids, and alkylamines, and organic surface treatment agents such as silane coupling agents and organosilicon compounds such as silane.
[0041] The method for producing the aniline black particle powder of the present invention will be described below, but the present invention is not limited thereto.
[0042] In the method for producing nigrosine particles of the present invention, the aromatic amine as the starting material is preferably aniline as the main component. That is, it can be an aromatic amine such as methylaniline, ethylaniline, toluidine, aminonaphthalene, or a nitrogen-containing heterocyclic compound such as pyrrole or pyridine. Alternatively, it can be a combination of two or more thereof, or a copolymer.
[0043] In the method for producing the aniline black particle powder of the present invention, any one of aromatic amines or acid salts of aromatic amines represented by aniline or acid salts of aniline as starting materials or a mixture thereof is dispersed or dissolved in water in a reaction tank, and adjusted to a predetermined pH value with an acid to prepare an acidic aqueous solution. An oxidant and a catalyst are added to the acidic aqueous solution to make it oxidatively polymerized to form a reaction solution. Preferably, the oxidant is added dropwise to the above-mentioned reaction tank while stirring to make the starting materials such as aniline undergo oxidative polymerization. An alkali-soluble resin aqueous solution dissolved under alkaline conditions is added dropwise to the solution after the reaction containing aniline black, and further stirred. Then, it is neutralized with an alkali agent, filtered, washed with water, dried, and then pulverized to obtain the aniline black particle powder of the present invention. Among them, as candidate substances for the catalyst, metals or metal salts can be cited. The metal or the metal salt can be added after being prepared into a uniform aqueous solution in advance or can be added dropwise simultaneously with the oxidant.
[0044] When a more uniform coating operation of the alkali-soluble resin is required, dispersion may be performed using a media disperser such as a bead mill or a media-free disperser such as a CLEARMIX, FILMIX, or ultrasonic homogenizer before or during the coating treatment of aniline black.
[0045] As the acid for adjusting to a predetermined pH, for example, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, boric acid, tetrafluoroboric acid, perchloric acid, periodic acid, formic acid, acetic acid, citric acid, oxalic acid, adipic acid, etc. can be cited, and they can be used alone or as a mixture. Among them, the concentration of the acidic aqueous solution also depends on the type of acid, and is usually 0.1 to 20% by weight, preferably about 0.2 to 15% by weight.
[0046] As the oxidizing agent, there can be mentioned dichromates such as potassium dichromate and sodium dichromate, persulfates such as ammonium persulfate, sodium persulfate and potassium persulfate, hydrogen peroxide, oxygen, etc., which can be used alone or as a mixture. The amount of the oxidizing agent used is preferably 0.1 to 10 moles, more preferably 0.5 to 5 moles, relative to 1 mole of the starting raw material such as aniline. In addition, the oxidizing agent is preferably added slowly to the reaction solution. The addition of the oxidizing agent usually takes 10 minutes to 10 hours, preferably 20 minutes to 5 hours, thereby controlling the oxidative polymerization rate. Due to this control, the particle size of the obtained aniline black can also be controlled.
[0047] As the metal or metal salt that can be used as the catalyst, copper sulfate, copper chloride, vanadium oxide, iron, ferric chloride, ferric nitrate, ferric sulfate, ferrous chloride, ferrous nitrate, ferrous sulfate, iron-EDTA chelate, platinum chloride, gold chloride or silver nitrate can be mentioned, which can be used alone or as a mixture. The amount of the catalyst used is usually preferably 0.01 to 1 mole, more preferably 0.02 to 0.5 mole, relative to 1 mole of the starting raw material such as aniline.
[0048] By adding an oxidizing agent and a catalyst to the reaction solution, the oxidative polymerization reaction of the starting material such as aniline proceeds. At this time, the catalyst decomposes the oxidizing agent to generate OH radicals, which can promote the oxidative polymerization reaction.
[0049] The reaction temperature is not particularly limited, and the reaction may be carried out usually at 10 to 70° C., preferably 20 to 60° C. After the addition of the oxidizing agent, the reaction solution is usually stirred for 10 minutes to 10 hours, preferably 20 minutes to 10 hours.
[0050] Alkali-soluble resins are dissolved in water under alkaline conditions. As alkaline agents for dissolving the resin, both inorganic compounds and organic compounds can be used. As inorganic compounds, hydroxides such as sodium hydroxide or potassium hydroxide, or carbonates such as sodium carbonate, etc. can be mentioned. As organic compounds, trialkanolamines such as triethanolamine or triisopropanolamine, etc. can be mentioned. The concentration of the alkali-soluble resin aqueous solution at this time is preferably 0.5 to 10.0%. In addition, the above-mentioned alkali-soluble resin aqueous solution is preferably added to the reaction solution slowly. It usually takes 15 minutes to 1 hour, preferably 20 minutes to 50 minutes to add the alkali-soluble resin aqueous solution, thereby enabling the resin to be evenly coated on the aniline black particles. The temperature of the reaction solution at this time is preferably 20 to 80°C.
[0051] The generated nigrosine and the reaction solution are both strongly acidic, so the pH is adjusted to a range of 4.0 to 9.0 using an alkali agent. The pH is preferably adjusted to a range of 5.0 to 8.0. If necessary, the mixture may be heated and stirred at 20 to 95° C. for 30 minutes to 1 hour.
[0052] As the alkali agent for the solution after the neutralization reaction, both inorganic compounds and organic compounds can be used. As inorganic compounds, hydroxides such as sodium hydroxide and potassium hydroxide, or carbonates such as sodium carbonate can be mentioned. As organic compounds, trialkanolamines such as triethanolamine and triisopropanolamine can be mentioned.
[0053] After neutralization with an alkali agent, filtration, water washing, drying and pulverization are carried out according to a conventional method to obtain the aniline black of the present invention.
[0054] Next, the resin composition containing aniline black of the present invention will be described.
[0055] In the resin composition of the present invention, it is preferred to mix a polyurethane resin composition. In addition, it is preferred to mix additives such as a lubricant, a plasticizer, an antioxidant, an ultraviolet light absorber, and various stabilizers as needed. These mixed substances become the constituent substrate of the resin composition.
[0056] As the mixing ratio of aniline black in the resin composition of the present invention, the usage amount of aniline black is preferably in the range of 0.01 to 200 parts by weight relative to 100 parts by weight of the above-mentioned constituent substrate. If considering that the resin composition maintains the flexibility as a resin while developing color, the aniline black is preferably 0.05 to 100 parts by weight, and more preferably 0.1 to 50 parts by weight.
[0057] The amount of the additive may be 50% by weight or less based on the total amount of aniline black and the polyurethane resin. If the content of the additive exceeds 50% by weight, the moldability of the resin composition decreases.
[0058] The lightness L* value of the resin composition of the present invention can be expressed by a chromaticity index based on the evaluation method described later, similar to the evaluation of aniline black, and the blackness is indicated by the lightness L* value. Preferably, the L* value is 15.0 or less, in which case the blackness is excellent. When the L* value exceeds 15.0, it is difficult to say that the blackness is excellent. A more preferred L* value is 14.0 or less. A further preferred L* value is 12.0 or less.
[0059] The method for producing the resin composition of the present invention will be described below, but the present invention is not limited thereto.
[0060] The resin composition of the present invention is produced by fully mixing aniline black and resin in advance, then using a mixer or extruder to apply strong shearing action under heating to break up the aggregates of aniline black, so that the aniline black is evenly dispersed in the resin, and then molding into a shape corresponding to the target.
[0061] Next, the aqueous dispersion containing the water-soluble polyurethane resin containing aniline black of the present invention will be described.
[0062] In the aqueous dispersion containing the water-soluble polyurethane resin of the present invention, water, an aqueous dispersion medium, a surfactant, a pigment dispersant, a water-soluble polyurethane resin, a pH adjuster, a defoamer, etc., and an extender pigment as required are preferably mixed. These mixed substances become the constituent base material of the aqueous dispersion.
[0063] As the mixing ratio of aniline black in the aqueous dispersion of the present invention, the usage amount of aniline black is preferably in the range of 0.1 to 200 parts by weight relative to 100 parts by weight of the substrate constituting the dispersion. In consideration of the color development and viscosity of the dispersion, it is more preferably 0.1 to 100 parts by weight, and further preferably 0.1 to 50 parts by weight.
[0064] As the resin, a water-soluble polyurethane resin may be used alone or in combination with a water-soluble alkyd resin, a water-soluble melamine resin, a water-soluble acrylic resin, or a water-soluble polyurethane emulsion resin.
[0065] As the aqueous dispersion medium, alcohols such as butanol, glycerin, butyl cellosolve, and the like are preferably used.
[0066] As the defoaming agent, a known defoaming agent is preferably used, for example, NOPCO 8034 (trade name), SN Deformer 477 (trade name), SN Deformer 5013 (trade name), SN Deformer 247 (trade name), SN Deformer 382 (trade name) (all of which are produced by SAN NOPCO LIMITED), ANTIFOAM 08 (trade name), EMULGEN 903 (trade name) (all of which are produced by Kao Corporation), etc.
[0067] The viscosity of the aqueous dispersion of the present invention is preferably 20.0 mPa·s or less. More preferably, it is 10.0 mPa·s or less. When the viscosity exceeds 20 mPa·s, it is difficult to adjust the properties of the coating formed using a rod coater. The lower limit of the viscosity is preferably 1.0 mPa·s. Even when the viscosity is less than 1.0 mPa·s, it is difficult to adjust the properties of the coating.
[0068] Regarding the storage stability of the aqueous dispersion of the present invention, the viscosity increase rate obtained by the evaluation method described below is preferably 20% or less, and more preferably 10% or less.
[0069] The method for producing the aqueous dispersion of the present invention will be described below, but the present invention is not limited thereto.
[0070] The aqueous dispersion of the present invention is preferably produced by mixing nigrosine, water and additives, dispersing using a media disperser such as a bead mill or a media-free disperser such as a CLEARMIX, FILMIX or ultrasonic homogenizer, and then performing post-treatment such as filtration. In order to improve the dispersion stability, the nigrosine particles may be subjected to self-dispersion treatment or microencapsulation treatment to modify the surface thereof.
[0071] <Function>
[0072] The aniline black particle powder of the present invention is a aniline black particle powder coated with 3 to 15% by weight of an alkali-soluble resin having an acid value of 150 to 350 mgKOH / g. After the aniline black reacts, an aqueous solution of the alkali-soluble resin dissolved under alkaline conditions is slowly added and stirred for a certain period of time, thereby forming aniline black with the resin uniformly coated on the surface of the pigment. Since the alkali-soluble resin is added under an acidic environment, the resin is insoluble and will not be washed away even by water washing. The inventor of the present invention speculates that by coating the surface of the aniline black particles with an insoluble resin, direct contact with the waterborne polyurethane resin is suppressed, and the modification of the waterborne polyurethane resin is suppressed, thereby preventing the coating from becoming thicker and gelling over time.
[0073] Example
[0074] Representative embodiments of the present invention are as follows.
[0075] Regarding the average particle size of the primary particles of the aniline black of the present invention, the specific surface area BET value was measured, and the spherical conversion value was calculated from the value by mathematical formula 1 to obtain the average particle size of the primary particles. Here, ρ shown in mathematical formula 1 is the true density of the particles, which is calculated from the true density of aniline black (the true density of aniline black obtained by using sodium dichromate as an oxidant is 2.083 g / mL, and the true density of aniline black obtained by using hydrogen peroxide as an oxidant is 1.36 g / mL).
[0076] <Mathematical formula 1>
[0077] Average particle size of primary particles of aniline black [μm] = 6 / (BET value × ρ)
[0078] The specific surface area BET value was measured by a BET method using nitrogen. The apparatus used was Monosorb MS-21 (manufactured by QUANTA CHROME).
[0079] As the pH value of the aniline black powder of the present invention, the pH value of the supernatant shown below is measured in accordance with JIS Z8802-7. That is, 5 g of the sample is weighed in a 300 ml conical flask, 100 ml of boiling pure water is added, and the mixture is heated and kept in a boiling state for about 5 minutes. Then, the mixture is covered with a stopper and cooled to room temperature, and water corresponding to the amount reduced by boiling is added, the mixture is covered with a stopper again, shaken for 1 minute, and then left to stand for 5 minutes.
[0080] The viscosity of the aqueous dispersion of the present invention is measured using an E-type viscometer TV-30 (manufactured by Toki Sangyo Co., Ltd.).
[0081] The storage stability of the aqueous dispersion of the present invention is evaluated by obtaining the yield value. The yield value after being kept at 25°C for 21 days is measured using an E-type viscometer TV-30 (manufactured by Toki Sangyo Co., Ltd.), calculated, and evaluated in three levels. The yield value is obtained by measuring the viscosity of the ink composition at different shear rates and using the Casson formula. The smaller the yield value, the smaller the aggregation degree of the pigment is estimated to be.
[0082] A: Yield value is less than 0.1dPa
[0083] B: Yield value exceeds 0.1dPa and is less than 1.0dPa
[0084] C: Yield value exceeds 1.0dPa
[0085] The lightness (blackness) of aniline black was evaluated using the aqueous dispersion of the present invention. The dispersion was coated using a bar coater, and the obtained coated sheet was measured for lightness (blackness: L* value) and hue and chroma (a* value, b* value) of the chromaticity index using a spectrophotometer X-Rite 939 (manufactured by X-Rite) in accordance with the provisions of JIS Z8729 in the same manner as the evaluation of the resin composition.
[0086] The degree of blackness of the aniline black of the present invention was evaluated in the following four levels.
[0087] A: L* below 12.0
[0088] B: L* is more than 12.0 and less than 15.0
[0089] C: L* is more than 15.0 and less than 20.0
[0090] D: L* more than 20.0
[0091] <Manufacturing of Aniline Black>
[0092] Embodiment 1:
[0093] 50 parts by weight of aniline were added to 50.4 parts by weight of 35% hydrochloric acid (17.6 parts by weight in terms of hydrochloric acid), 31.8 parts by weight of 75% sulfuric acid (23.9 parts by weight in terms of sulfuric acid) and 840 parts by weight of water to prepare an acidic aqueous solution. Then, while stirring and mixing at a liquid temperature of 25°C, an aqueous solution of 14 parts by weight of copper (II) sulfate 5 hydrate dissolved in 140 parts by weight of water was added, and an aqueous solution of 123.5 parts by weight of 68% sodium dichromate (86 parts by weight in terms of potassium dichromate) diluted in 150 parts by weight of water was added dropwise over 30 minutes. After stirring at a liquid temperature of 50°C for 5 hours to complete the reaction, an aqueous solution of 6.6 parts by weight of styrene-acrylic acid copolymer JONCRYL 67 (manufactured by BASF) dissolved in 120 parts by weight of a 10% sodium hydroxide aqueous solution was added, and stirred for 30 minutes. Then, the mixture was filtered and washed with water, and the paste was dried at 60°C and pulverized to obtain a black pigment. (Aniline Black-1). In addition, since almost no eluted resin was confirmed in the filtrate after the coating treatment with the resin, it was confirmed that the total amount of the added resin was coated.
[0094] The average particle size of the primary particles of Nigrosine-1 is 8.0 μm due to the BET value. 2 / g, which is converted to 0.36 μm using Mathematical Formula 1. The powder pH is 4.2.
[0095] The electron microscope photograph of the obtained aniline black is shown in Figure 1 middle. Figure 1It was found that a uniform coating layer with a thickness of about 10 nm was formed on the surface of the particles of aniline black. Other parts were also confirmed, and it was confirmed that the surface of the particles of aniline black was uniformly coated with the resin almost entirely.
[0096] Embodiment 2~4:
[0097] Aniline black was obtained in the same manner as in Example 1 except that the amount and type of the alkali-soluble resin were changed.
[0098] Embodiment 5:
[0099] 30 parts by weight of aniline were added to 50.4 parts by weight of 35% hydrochloric acid (17.6 parts by weight in terms of hydrochloric acid) and 1050 parts by weight of water to prepare an acidic aqueous solution. Then, while stirring and mixing at a liquid temperature of 25°C, an aqueous solution of 1.74 parts by weight of ferric chloride hexahydrate dissolved in 33 parts by weight of water was added, and 300 parts by weight of 9% hydrogen peroxide water (27 parts by weight in terms of hydrogen peroxide) was added dropwise over 7 hours, and the mixture was stirred for 12 hours. Then, after stirring at a liquid temperature of 50°C for 2 hours to complete the reaction, an aqueous solution of 4.0 parts by weight of styrene-acrylic acid copolymer JONCRYL67 (manufactured by BASF) dissolved in 80 parts by weight of a 10% sodium hydroxide aqueous solution (5% by weight relative to aniline black) was added, and the mixture was stirred for 30 minutes. Then, the mixture was filtered and washed with water, and the paste was dried and pulverized at 50°C to obtain a black pigment. (Aniline Black-5).
[0100] The average particle size of the primary particles of nigrosine-5 is 12.0 μm, as the BET value is 2 / g, which is converted to 0.37 μm using Formula 1. The powder pH is 4.4.
[0101] Embodiment 6:
[0102] Aniline black was obtained in the same manner as in Example 5 except that the amount and type of the alkali-soluble resin were changed.
[0103] The production conditions of these examples are shown in Table 1. Table 1 shows the weight parts when each raw material is 100%. Among them, only the amount of addition of the alkali-soluble resin is recorded in the weight % of the generated aniline black. For example, in Example 1, 5 weight % of styrene-acrylic acid copolymer JONCRYL 67 (manufactured by BASF) is used relative to 131.7 weight parts of aniline black generated, and in Example 5, 5 weight % of styrene-acrylic acid copolymer JONCRYL 67 (manufactured by BASF) is used relative to 79.0 weight parts of aniline black generated.
[0104] The properties of the obtained aniline black are shown in Table 2. The properties include the average particle size of primary particles of aniline black, the average particle size of primary particles of the composite oxide fine particles, and the powder pH.
[0105] Comparative Example 1:
[0106] 50 parts by weight of aniline were added to 50.4 parts by weight of 35% hydrochloric acid (17.6 parts by weight in terms of hydrochloric acid), 31.8 parts by weight of 75% sulfuric acid (23.9 parts by weight in terms of sulfuric acid) and 840 parts by weight of water to prepare an acidic aqueous solution. Then, while stirring and mixing at a liquid temperature of 25°C, an aqueous solution of 14 parts by weight of copper sulfate (II) 5 hydrate dissolved in 140 parts by weight of water was added, and an aqueous solution of 123.5 parts by weight of 68% sodium dichromate (86 parts by weight in terms of potassium dichromate) diluted in 150 parts by weight of water was added dropwise over 30 minutes. Then, the mixture was stirred at a liquid temperature of 50°C for 5 hours, and a 10% sodium hydroxide aqueous solution was added to neutralize to pH 5.0. After the pH stabilized, the mixture was filtered and washed with water, and the paste was dried and pulverized at 60°C to obtain a black pigment that does not contain an alkali-soluble resin. (Aniline Black-7).
[0107] The average particle size of the primary particles of Nigrosine-7 is 8.5 μm due to the BET value. 2 / g, which is converted to 0.34 μm using Formula 1. The powder pH is 4.1.
[0108] The electron microscope photograph of the obtained aniline black is shown in Figure 2 middle.
[0109] Comparative Example 2:
[0110] With reference to Japanese Patent Application Laid-Open No. 2002-60647, Nigrosine 7 synthesized in Comparative Example 1 was neutralized to pH 9.0 to obtain a black pigment (Nigrosine 8) not containing an alkali-soluble resin.
[0111] Comparative Examples 3 to 6:
[0112] Aniline black was obtained in the same manner as in Comparative Example 1 except that the amount and type of the alkali-soluble resin were changed.
[0113] Comparative Example 7:
[0114] With reference to Japanese Patent Publication No. 10-060314, aniline black was coated with an insoluble resin acrylic resin. That is, after synthesizing aniline black-7 in Comparative Example 1, an aqueous solution of 20.0 parts by weight of acrylic resin: Watersol S744 (solid content concentration 40%, manufactured by DIC) (8 parts by weight in terms of solid content, 10% by weight relative to aniline black) diluted in 140 parts by weight of water was added and stirred for 30 minutes. Then, the mixture was filtered and washed with water, and the paste was dried at 60°C and pulverized to obtain a black pigment (aniline black-13).
[0115] Comparative Example 8:
[0116] With reference to Japanese Patent Publication No. 10-060314, aniline black was coated with an insoluble resin polyurethane resin. That is, after synthesizing aniline black-7 in Comparative Example 1, an aqueous solution of 26.7 parts by weight (8 parts by weight in terms of solid content, 10% by weight relative to aniline black) of polyurethane resin Super flex 620 (solid content concentration 30%, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) diluted in 130 parts by weight of water was added and stirred for 30 minutes. Then, the mixture was filtered and washed with water, and the paste was dried at 60°C and pulverized to obtain a black pigment (aniline black-14).
[0117] The production conditions of these comparative examples are shown in Table 1 according to the description of the examples, and the properties of the obtained aniline black are shown in Table 2. As shown in Table 2, the aniline black-8 of the comparative example had a powder pH of 6.8.
[0118] The electron microscope photograph of the obtained aniline black is shown in Figure 3 . Figure 3 It is found that a part of the surface of the aniline black particles is coated with the resin.
[0119]
[0120] [Table 2]
[0121] name <![CDATA[BET(m 2 / g)]]> Average particle size of primary particles (μm) Powder pH(-) Example 1 Nigrosine-1 8 0.36 4.2 Example 2 Nigrosine-2 7.9 0.36 4.3 Example 3 Nigrosine-3 7.7 0.37 4.1 Example 4 Nigrosine-4 8.2 0.35 4.5 Example 5 Nigrosine-5 12.0 0.37 4.4 Example 6 Nigrosine-6 12.2 0.37 4.4 Comparative Example 1 Nigrosine-7 8.5 0.34 4.1 Comparative Example 2 Aniline Black-8 8 0.36 6.8 Comparative Example 3 Aniline Black-9 7.8 0.37 4.1 Comparative Example 4 Nigrosine-10 7.9 0.36 4.5 Comparative Example 5 Nigrosine-11 8.2 0.35 4.3 Comparative Example 6 Nigrosine-12 8.3 0.35 4.2 Comparative Example 7 Nigrosine-13 7.9 0.36 4.2 Comparative Example 8 Aniline Black-14 8.2 0.35 4.3
[0122] <Manufacturing of Aqueous Dispersion>
[0123] Embodiment 7:
[0124] The aniline black-1 obtained in Example 1 was used to prepare the aqueous dispersion composition according to the following ratio: 50 parts by weight of glass beads were mixed and dispersed together with a paint shaker for 180 minutes to prepare an aqueous dispersion.
[0125]
[0126] The viscosity of the obtained aqueous dispersion was 8.29 mPa·s, and the viscosity of the aqueous dispersion after being kept at 25° C. for 21 days was 8.57, the viscosity increase rate was 3.4%, the yield value was 0.0052 dPa, and the storage stability was A. That is, the storage stability of the aqueous dispersion was good.
[0127] In order to observe the blackness of the aniline black-1 obtained in Example 7, a coating film was prepared on a glass plate using a bar coater with a WET film thickness of 12 μm, after the dispersion of Example 7 was kept at 25°C for 21 days. The dispersion was baked at 120°C for 30 minutes to prepare a coating sheet (coating film thickness: about 3 μm). The L* value of the obtained coating sheet was 10.03, and the blackness of the aniline black-1 was A.
[0128] Examples 8 to 12, Comparative Examples 9 to 16:
[0129] An aqueous dispersion was obtained in the same manner as in Example 7 except that the type of nigrosine particle powder was changed.
[0130] The properties of the obtained aqueous dispersion and the obtained coated sheet are shown in Table 3. In Examples 7 to 12, the viscosity of the aqueous dispersion after being kept at 25° C. for 21 days was 20.0 mPa·s or less, the viscosity increase rate was also 10% or less, the yield value was 0.1 dPa or less, and the storage stability was A. In Comparative Examples 9 to 16, in all Comparative Examples except Comparative Example 10, the aqueous dispersion gelled after being kept at 25° C. for 21 days. In Comparative Example 10, the viscosity of the aqueous dispersion after being kept at 25° C. for 21 days was 43.01 mPa·s, the viscosity increase rate was 403%, and the yield value was 5.78 dPa, and good storage stability was not obtained.
[0131] In addition, regarding the blackness, in Examples 1 to 6, the L* value of the obtained coated sheets was 15.0 or less, and the blackness was determined to be B or higher. However, in Comparative Examples 9 to 16, in all Comparative Examples except Comparative Example 10, the aqueous dispersion gelled after being kept at 25° C. for 21 days, and in Comparative Example 10, the L* value of the obtained coated sheet was 16.87, and a sufficient blackness was not obtained.
[0132]
[0133] As described above, it is understood that the aqueous dispersion of the present invention is excellent in storage stability and blackness.
[0134] Industrial Applicability
[0135] The aniline black particle powder of the present invention has excellent blackness in the use of synthetic leather coatings, etc., and can prevent the viscosity increase or gelation of resin over time. Therefore, in addition to the previous uses such as coatings and printing inks, it is also suitable for use in fields such as non-magnetic developers for electronic photography or electronic devices as black matrix colorants. In addition, the aniline black of the present invention does not contain harmful substances such as chromium ions or copper ions, and is also suitable for various uses such as cosmetics, coatings, printing inks, and inkjet inks. In addition, in the aqueous dispersion containing the aniline black, the blackness is excellent, and the viscosity increase or gelation of resin over time can be prevented. Therefore, it is suitable for use in fields such as non-magnetic developers for electronic photography or electronic devices as black matrix colorants, or various uses such as cosmetics, coatings, printing inks, and inkjet inks.
Claims
1. A nigrosine particle powder, which is a nigrosine particle powder coated with an alkali-soluble resin, wherein the nigrosine particle powder is characterized in that: The acid value of the alkali-soluble resin is 150-350 mgKOH / g, and the coating amount of the alkali-soluble resin is 3-15% by weight. The average particle size of the primary particles is 0.05 to 1.0 μm.
2. The nigrosine particle powder according to claim 1, characterized in that: The alkali-soluble resin is one or more resins selected from styrene-acrylic acid copolymer, styrene-maleic acid copolymer and rosin-modified resin.
3. The nigrosine particle powder according to claim 1 or 2, characterized in that: The thickness of the coating layer formed of the alkali-soluble resin is 2 to 50 nm.
4. A polyurethane resin composition comprising the aniline black particle powder according to any one of claims 1 to 3. 5 . An aqueous dispersion containing a water-soluble polyurethane resin, comprising the nigrosine particle powder according to claim 1 .
Citation Information
Patent Citations
Aniline black colorant composition and black pigment composition using the same
JP2002060647A
Aqueous pigment dispersion and its production
JP1996073787A
Black drawing material
JP1998060314A